Replication of Epigenetic Postpartum Depression Biomarkers and Variation with Hormone Levels - Osborne, Lauren; Clive, Makena; Kimmel, Mary; Gispen, Fiona; Guintivano, Jerry; Brown, Tori; Cox, Olivia; Judy, Jennifer; Meilman, Samantha; Braier, Aviva; Beckmann, Matthias; Kornhuber, Johannes; et al. (Neuropsychopharmacology, 2016)
DNA methylation variation at HP1BP3 and TTC9B is modified by estrogen exposure in the rodent hippocampus and was previously shown to be prospectively predictive of postpartum depression (PPD) when modeled in antenatal blood. The objective of this study was to replicate the predictive efficacy of the previously established model in women with and without a previous psychiatric diagnosis and to understand the effects of changing hormone levels on PPD biomarker loci. Using a statistical model trained on DNA methylation data from N=51 high-risk women, we prospectively predicted PPD status in an independent N=51 women using first trimester antenatal gene expression levels of HP1BP3 and TTC9B, with an area under the receiver operator characteristic curve (AUC) of 0.81 (95% CI: 0.69-0.92, p<5 × 10(-4)). Modeling DNA methylation of these genes in N=240 women without a previous psychiatric diagnosis resulted in a cross-sectional prediction of PPD status with an AUC of 0.81 (95% CI: 0.68-0.93, p=0.01). TTC9B and HP1BP3 DNA methylation at early antenatal time points showed moderate evidence for association to the change in estradiol and allopregnanolone over the course of pregnancy, suggesting that epigenetic variation at these loci may be important for mediating hormonal sensitivity. In addition both loci showed PPD-specific trajectories with age, possibly mediated by age-associated hormonal changes. The data add to the growing body of evidence suggesting that PPD is mediated by differential gene expression and epigenetic sensitivity to pregnancy hormones and that modeling proxies of this sensitivity enable accurate prediction of PPD.
EVALuna2:23791